Event-triggered non-fragile control for linear systems with actuator saturation and disturbances - Liu, Dan; Yang, Guang-Hong (Information sciences, 2018)
This paper investigates the problem of event-triggered non-fragile dynamic output feedback controller design for linear systems with actuator saturation and disturbances. The controller to be designed is supposed to include additive gain variations. By using Lyapunov stability theory and adding slack matrix variables, new sufficient conditions are derived to design the event-triggered parameters and the controller gains. Compared with the existing non-fragile dynamic output feedback controller design methods, the structural restriction on the Lyapunov matrix is relaxed. The effectiveness of the proposed method is demonstrated by two examples.